Propagação vegetativa de jabuticabeira - Sasso, Simone Aparecida Zolet (2009)
The jabuticaba tree is a specie of difficult vegetative propagation and an efficient protocol has not been defined yet. The aim of this work was to test the efficiency of vegetative propagation techniques for jabuticaba tree and develop an efficient protocol for disinfection and initial establishment of in vitro explants. It was tested the rooting potential of wood cutting of P. cauliflora, utilizing four concentrations of Indolbutiric Acid - IBA (0, 2000 , 4000 and 6000 mg L-1) and two procedures (cross section and cuttings girdling); and the rooting potential of softwood terminal cuttings of P. cauliflora, utilizing five concentrations of IBA (0, 2000, 4000, 6000 and 8000 mg L-1) in two periods of implantation (October and December 2007). The rooting potential of cuttings was evaluated after 180 days of the beginning of the experiments. It was also tested the compatibility of grafting of three species of jabuticaba tree (P. cauliflora, P. trunciflora, P. jaboticaba) on rootstocks of P. cauliflora, and two periods (May and August). It was evaluated the survival percentage of grafting, number and size of shoots, after 90 days of the beginning of the experiment. For air layering techniques, it was tested two diameters of branch (1.0-1.5 cm and 2.0-2.5 cm) and two widths of girdling (1.5 cm and 3.0 cm) in P. cauliflora. It was evaluated the rooting percentage, and number and size of roots, 180 days after the beginning of the experiment. It was also tested the period of immersion (5, 10, 15 minutes) in 1,25% sodium hypochlorite solution in the in vitro establishment of shoot and root of the seedlings explants of P. trunciflora. After 45 days of incubation it was evaluated the percentage of contamination and number of shoots and leaves in each explant. It was observed that rooting of wood cutting is dependent of application of IBA, so the biggest rooting percentage (50%) was obtained in biggest concentration of IBA (6000mg L-1) associated with cross section. For the softwood terminal cuttings, the rooting was small (maximum of 10%). Meantime, exist the potential of rooting, and, changes of technique must be tested for maximization. The grafting and the air layering techniques are recommended for jabuticaba tree propagations, because this techniques provide high percentage of plants formation. There is visible compatibility between the three species grafted on rootstocks of P. cauliflora. The utilization of grafts collected from plants in fructification should be avoided, because they reduce the percentage of plants establishment. In air layering techniques, branches with diameter of 2.0 cm provides higher percentage of rooting and the biggest number and size of roots in relation of branches with small diameter (1.0 to 1.5 cm). The utilization of less time in immersion (five minutes) in 1,25% sodium hypochlorite solution is efficient for shoots explants disinfestations of jabuticaba tree seedlings and allows the initial in vitro establishment, providing development of shootings.